Sustainability and OHS Global Reporting in Petrochemical Industries: The GRI Reporting Standard and Corporate Social Responsibility - Alfadhli, Abdulaziz (East Carolina University, 2019)
Sustainability reporting, an aspect of corporate social responsibility (i.e., CSR), is the practice of measuring, disclosing, and being accountable to internal and external stakeholders for organizational performance and the goal of sustainable development. Sustainability reporting is a broad term used to describe reporting on a firm economic, environmental, and social impacts. A sustainability report should provide a balanced and reasonable representation of the sustainability performance of a reporting organization, which includes both positive and negative contributions. (Global Reporting Initiative, 2011, p. 3). This paper describes the level of occupational health and safety reporting for the Chemical and Engineering News (C&EN) top 50 global chemical companies. The Global Reporting Initiative (GRI) standard GRI: 403 Occupational Health and Safety 2018 was used as the basis for investigation. This paper explains how the growing interest in corporate social responsibility can contribute to improving the implementation of adequate systems of prevention and protection. Occupational health and safety in the petrochemical sector has become a great public interest and is associated with exposure risks to a variety of toxic chemicals and other agents which fuels questions surrounding the necessary strategies required for safer petrochemical industries. The increasing pressure from challenges impeding the improvement of performance requires the need for establishing strategic roles aimed at restoring safety design systems while improving the roles of national health safety standards and corporate staff. This paper focuses on a set of three strategies aimed at improving occupational health and safety in the petrochemical sector including: (1) national/international standards and regulating agencies, (2) the role of health staff, and (3) strategic safety culture management. This is accomplished using a qualitative research design based on secondary data sources. Descriptive methods were used to analyze the qualitative data and the results presented through frequency tables, graphs, correlation matrices, and mean scores across study populations. The findings from this study reveal that a company's safety culture is a function of national OHS policies, safety rules and procedures, incentives, training, communication, worker involvement, safety manager commitment, and employee safety behavior. Safety culture is additionally observed as a reflection of the safety performance of firms in the petrochemical industry. Health staff can contribute towards health and safety training, the development of positive safety attitudes, and safety compliance. These statistics and evaluations are important because their role in establishing occupational health practices have been found to be effective in promoting, protecting, and rehabilitating the health and well-being of people. The study concludes that it is essential to establish the roles of health staff, national OHS standards, and safety culture management, and the means of achieving them.
Keywords: Global Reporting Initiative(GRI); Sustainable development reporting; Social responsibility of business; Industrial safety